Motivasi Berprestasi Guru SD Perempuan Sebagai Tulang Punggung Keluarga, Sebagai Penulis, Sebagai Finalis Guru Berprestasi Bidang Matematika Tingkat Provinsi, Sebagai Guru Les Privat dan Guru Olimpiade Matematika - Apriliyani, Rani Ika; Fadillah, Ainayah Safira; Imtihanah, Nur; Novita, Erlina Maya; Septiani, Maidatul (Neolectura, 2024)
The family is based on marital ties consisting of a husband, wife and unmarried children. With the turning of time, the family economy is getting bigger in daily needs, causing a mother to have to participate in earning a living to meet her needs in a family. The reason behind a housewife becoming the backbone of the family, there are two factors, namely internal and external factors. The research method used is qualitative research method. According to Creswell (2008), qualitative research methods define it as an approach or search to explore and understand a central symptom. The results of qualitative research are strongly influenced by the views, thoughts, and knowledge of the researcher because the data is interpreted by the researcher. This method does not use detailed questions, questions start with the general then go into detail. The description of achievement motivation in the subject is seen where the subject wants to show and prove to the old school where the subject teaches that the subject is able to develop. There are many factors that make the subject obtain achievement motivation in herself, namely: The subject has an environment with a high intellectual group, the subject is motivated by other writers in living life as a writerSubject is a teacher and also a housewife. The subject started teaching in 1997 and first taught in high school and then vocational school and stopped teaching due to marriage and then when he had children. The subject's initial motivation for teaching was only to prove that the subject could teach then when he stopped teaching and then returned to teaching his motivation was to replace the role of his husband who was not working at that time.